THE LOCAL WISDOM OF INDIGENOUS COMMUNITIES, RELIGIOUS LEADERS, AND INTELLECTUALS IN MITIGATING THE SOCIAL IMPACTS OF ILLEGAL GOLD MINING IN WEST PASAMAN, WEST SUMATRA - Sahrul, Sahrul; Daulai, Afrahul Fadhila (MIQOT: Jurnal Ilmu-ilmu Keislaman, 2025)
This study explores the role of indigenous, religious, and intellectual institutions in mitigating the social impacts of illegal gold mining on communities in West Pasaman, West Sumatra. Employing a qualitative research design, data were collected through interviews and observations involving ten key informants. Data analysis was conducted using the framework proposed by Miles and Huberman. The findings reveal that illegal gold mining has led to significant social consequences, including social conflict, economic disparities, moral degradation, and the proliferation of drug and alcohol abuse. These pressing issues have garnered serious attention from Tigo Tungku Sajarangan, a traditional leadership structure, which collaborates with the Nagari Customary Court to address these challenges. This collaboration involves various stakeholders, including nagari leaders, the Nagari Traditional Council, the Indonesian Ulema Council (MUI) of West Pasaman, local Islamic preachers, as well as members of Muhammadiyah and Nahdlatul Ulama. Additionally, non-governmental organizations and diaspora communities also play an active role in these efforts. The initiatives undertaken through this collaboration include moral appeals, public awareness campaigns, and the imposition of customary sanctions. However, customary institutions lack the legal authority to prosecute criminal offenses, limiting their ability to enforce legal consequences. Nonetheless, their efforts contribute significantly to fostering social harmony and strengthening community resilience against the adverse effects of illegal gold mining.Keywords: Society, Impact, Illegal Gold Mining, Tigo Tungku Sajarangan